The Effectiveness of an Innovative Mobile Application in Self-Regulation and Metacognitive Awareness Among Eighth Grade Students in the Sultanate of Oman - Al-Hosni, Huda Ali Said; Al-Balushi, Sulaiman Mohammed; Al-Salmi, Asmaa Hamed; Al-Shukaili, Zahra Saif (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to evaluate the effectiveness of a gamified mobile application in enhancing self-regulation and metacognitive awareness among eighth-grade students in Oman during the COVID-19 pandemic. Using a quasi-experimental design, the study involved 63 students, divided into an experimental group (33 students) and a control group (30 students), with pre- and post-tests conducted. The researchers designed an innovative mobile application based on the gamification approach, which focuses on providing students with scientific concepts in various fields of science, and which was called (Dr.Electron). The self-regulation and metacognitive awareness scales used had reliability coefficients of (0.91) and (0.95), respectively. Results indicated significant improvements in the experimental group for both self-regulation and metacognitive awareness compared to the control group. However, no significant interaction between teaching method and gender was found for self-regulation, while a significant interaction was observed for metacognitive awareness. The study recommends the use of gamified educational apps to enhance student engagement, especially during crises like the COVID-19 pandemic.